Neural crest stem cells : breakthroughs and applications - Sieber-Blum, Maya (World Scientific Pub. Co., 2012)
The book offers readers an understanding of the development of neural crest cells, which is crucial as many birth defects and tumours are of neural crest origin. The neural crest is a transient tissue of the vertebrate embryo. It originates from the future spinal cord and neural crest stem cells emigrate from this location to various places in the embryo, giving rise to many different cell types and tissues. Neural crest derivatives include the peripheral nervous systems, endocrine cells such as the adrenal medulla, smooth musculature of the cardiac outflow tract and great blood vessels, as we.